Causal roles of skin microbiota in skin cancers suggested by genetic study - Zhu, Yuhang; Liu, Wanguo; Wang, Mei; Wang, Xu; Wang, Sibo (Frontiers in Microbiology, 2024)
Novelty and Impact: Previous MR analyses have focused on exploring the impact of gut microbiota on a multitude of diseases, but research on skin microbiota is still scarce. This is the first Mendelian randomization to report the causal association between skin microbiota and skin cancers. We identified 294 skin microbiota based on phylum, class, order, family, genus, and ASV level information from the first GWAS study across three skin microenvironments. This MR analysis revealed that the skin microbiota was bidirectionally causally associated with skin cancers, and had the potential to provide early diagnosis, preventive measures, and additional therapeutic options for skin cancers.